Strategies for Building a Successful Business while living a Happy and Balanced Life - Bjergegaard , Martin; Milne , Jordan; Aneet (Gyan Management Journal, 2013)
Winning without Losing offers 66 strategies to help increase the efficiency of working members of the team and create a successful working life while maintaining time and energy to enjoy their personal life to the full. Hard work which leads to success has to be invested at the cost of leisure, family and other relationships. Here is a book which breaks the myths of hard work and sacrifice; it shows that it is actually possible to put family, friends and other relalionships first and win without losing on many other precious gifts of life. Martin Bjergegaard and Jordan Milne have explained how to build a business into something big, sustainable and widely recognized - and still lead a happy, whole and balanced life. As many as 66 strategies to live a successful life without sacrificing people or things one loves have been divided in seven parts. Each strategy has a lesson which can in!ipire would-be entrepreneurs, hardcore business persons as well as someone who wants success without compromising on a balanced and good quality of life. The authors have learnt from 25 of their role models, including N R Naryana Murthy, who subscribe to the philosophy of getting ahead in different fields without a punishing schedule and without sacrificing their happiness.